2 plus 2 equals ?. (2015) - Briloff, Abraham J.; Tinker, Tony; Sy, Aida
Abe Briloff has passed away recently. The editors of the International Journal of Critical Accounting are updating his classics for publication. This article is a chapter, entitled, 2 plus 2 equals...? The article deals with auditing and financial statements. When Briloff wrote it first, there were big eight accounting firms in the USA. The BIG EIGHT firms, then were in charge of auditing the big corporation. The article raises interesting method of auditing that were twisted by big accounting firms. The article is a critic of failure of compliance of the most elementary GAAP rules and regulations as far as auditing of financial statements of listed corporations is involved. Interesting to see that Abe has predicted the ENRON, WorldCom, Xeros, Vivendi, you name it, saga of corporation frauds, auditing failures, etc. While we are re-publishing this great work, there are now only four big accounting firms in the USA.